Use of Body-Mounted Inertial Sensors to Objectively Evaluate the Response to Perineural Analgesia of the Distal Limb and Intra-articular Analgesia of the Distal Interphalangeal Joint in Horses With Forelimb Lameness - Rungsri P.K. (2014)
Diagnostic analgesia of the distal interphalangeal (DIP) joint is theoretically helpful to localize the source of pain in the foot to the joint and/or navicular bursa. However, it has been suggested that potential diffusion of local anesthetic agent to nearby distal limb nerves may anesthetize other areas of the foot. The objective of this study was to compare the results of palmar digital (PD) and abaxial sesamoid (AS) nerve blocks to intra-articular anesthesia of the DIP joint in horses with distal forelimb lameness. Palmar digital nerve block (group 1) or PD and AS nerve blocks (group 2) were used to abolish digital pain in 22 horses. The following day lameness was again evaluated in all horses before and 2, 5, and 10 minutes after DIP joint anesthesia. All lameness evaluations were performed objectively with a body-mounted inertial sensor system (Lameness locator; Equinosis LLC, Columbia, MO). In group 1 horses, overall improvement in group lameness was the same after DIP joint block, but only six showed positive response after DIP joint analgesia, five after 2 minutes, and one after 5 minutes. In group 2 horses, overall improvement in lameness was less after DIP joint block, with seven showing a positive response after DIP joint analgesia, one after 2 minutes, four after 5 minutes, and two after 10 minutes. Intra-articular analgesia of the DIP joint and perineural analgesia of the digit result in overlapping but unequal areas of analgesia. In addition, a time-dependent response was observed after DIP joint block with full effect requiring 5-10 minutes. © 2014 Elsevier Inc. All rights reserved.